Highly Automated QT Measurement Techniques in 7 Thorough QT Studies Implemented under ICH E14 Guidelines - Couderc, Jean-Philippe; Garnett, Christine; Li, Mike; Handzel, Robert; McNitt, Scott; Xia, Xiajuan; Polonsky, Slava; Zareba, Wojciech (Annals of noninvasive electrocardiology, 2011)
Thorough QT (TQT) studies are designed to evaluate potential effect of a novel drug on the ventricular repolarization process of the heart using QTc prolongation as a surrogate marker for torsades de pointes. The current process to measure the QT intervals from the thousands of electrocardiograms is lengthy and expensive. In this study, we propose a validation of a highly automatic‐QT interval measurement (HA‐QT) method. We applied a HA‐QT method to the data from 7 TQT studies. We investigated both the placebo and baseline‐adjusted QTc interval prolongation induced by moxifloxacin (positive control drug) at the time of expected peak concentration. The comparative analysis evaluated the time course of moxifloxacin‐induced QTc prolongation in one study as well. The absolute HA‐QT data were longer than the FDA‐approved QTc data. This trend was not different between ECGs from the moxifloxacin and placebo arms: 9.6 ± 24 ms on drug and 9.8 ± 25 ms on placebo. The difference between methods vanished when comparing the placebo‐baseline‐adjusted QTc prolongation (1.4 ± 2.8 ms, P = 0.4). The differences in precision between the HA‐QT and the FDA‐approved measurements were not statistically different from zero: 0.1 ± 0.1 ms (P = 0.7). Also, the time course of the moxifloxacin‐induced QTc prolongation adjusted for placebo was not statistically different between measurements methods. Ann Noninvasive Electrocardiol 2011;16(1):13–24